Pemanfaatan Teknik Kerjasama Kolaboratif pada Mata Pelajaran Ekonomi Guna Meningkatkan Berpikir Kritis Siswa - Ratna Tiharita (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract :There are many problems arise in learning proccess. It can be derived from human resources itself, teacher or student, infrastructure, methods, learning techniques which are less attractive. Learning techniques have an important role because it is able to develop the students’ potential. Critical thinking is a gift of God Almighty given to mankind for improvement in their lives. Therefore, critical thinking should be explored. There are a variety of learning techniques, but not always in accordance with the learning techniques of teaching materials. In the hope of critical thinking can be developed through the collaborative work techniques. In this case, intelligence is needed to make a teacher effective learning. Utilization engineering collaborative work on economic subjects is expected to be an alternative. This paper will discuss the urgency of what techniques utilizing collaborative work to improve students’ critical thinking. Keywords: technical cooperation collaborative; subjects economics; critical thinking. Abstrak: Banyak permasalahan muncul dalam pembelajaran. Hal ini dapat berasal dari sumber daya manusianya itu sendiri, yakni guru atau siswa, sarana prasarana, metoda, atau dari teknik pembelajaran yang kurang menarik. Teknik pembelajaran memiliki peran penting karena mampu menumbuhkembangkan potensi siswa. Berfikir kritis merupakan karunia Tuhan Yang Maha Esa yang diberikan kepada manusia untuk perbaikan dalam kehidupannya. Maka dari itu, berfikir kritis harus dieksplorasi. Ada beragam teknik pembelajaran, namun tidak selalu teknik pembelajaran sesuai dengan materi ajar. Di harapkan berfikir kritis dapat dikembangkan melalui teknik kerjasama kolaboratif. Dalam hal ini, Kecerdasan seorang guru diperlukan guna menjadikan pembelajaran efektif. Pemanfaatan teknik kerjasama kolaboratif pada mata pelajaran ekonomi diharapkan dapat menjadi alternatif. Makalah ini akan membahas tentang apa urgensinya memanfaatkan teknik kerjasama kolaboratif guna meningkatkan berfikir kritis siswa. Pengutipan: S. Tiharita, R. (2016). Pemanfaatan Teknik Kerjasama Kolaboratif pada Mata Pelajaran Ekonomi Guna Meningkatkan Berpikir Kritis Siswa. SOSIO DIDAKTIKA: Social Science Education Journal, 3(1), 2016, 9-16. doi:10.15408/sd.v3i1.3793.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i1.3793